Accelerating Health Reforms through Collective Action : Experiences from East Africa - Nkrumah, Yvonne; Mensah, Julia (2014)
The roots signify the origins and initial steps taken to build a coalition and the associated teething problems; the trunk represents efforts toward sustaining the organization s existence and growth; and the branches highlight the collective actions undertaken by the coalition in fulfillment of its aims and objectives. In preparing this book, and based on their unique experiences, Tanzania, Kenya, and Uganda respectively focus their chapters on the roots, trunk, and branches. To further the tree analogy, each country s chapter draws parallels or makes comparisons with what pertains in the other two countries, to show how they benefit from each other in an ongoing knowledge exchange. Chapter two (Putting Down Roots, Tanzania) has three main sections: an overview of the country context and health reform agenda; a discussion of the experiences of MSG-Pharma, Tanzania s multi-stakeholder body, in setting up a coalition, and lessons learned. These outline the reasons leading to the establishment of the multi-stakeholder group and describe how challenges met during its formation stages were overcome. Chapter three (growing a strong trunk, Kenya) provides insights into the approaches employed by Kenya s multi-stakeholder coalition, the Forum for Transparency and Accountability in Pharmaceutical Procurement (FoTAPP), in order to sustain the interest and commitment of key stakeholders. It presents a brief description of the Kenyan context in relation to the pharmaceutical sector, highlighting challenges in the sector, and the importance of a multi-stakeholder coalition amid other reform platforms. Chapter four (branching out and bearing fruits, Uganda) describes the opportunities, challenges, and rewards associated with designing and implementing a joint intervention in furtherance of the goals of the Medicines Transparency Alliance (MeTA), the coalition in Uganda. It also illustrates how the coalition has been Able to inform policy dialogue and reform efforts in the health sector.